1993
DOI: 10.1104/pp.103.3.763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boron on Proton Transport and Membrane Properties of Sunflower (Helianthus annuus L.) Cell Microsomes

Abstract: Boron deficiency and toxicity inhibit ATP-dependent H+ pumping and vanadate-sensitive ATPase activity in sunflower roots and cell suspensions..The effects of boron on H+ pumping and on passive H+ conductance, as well as on fluorescence anisotropy in KI-washed microsomes isolated from sunflower (Helianfhus annuus 1. cv Enano) cell suspensions, have been investigated. Boron deficiency reduced the total and vanadate-sensitive ATPase activities as well as the vanadate-sensitive ATP-dependent H+ pumping without aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…The suppressed expression of the H + -ATPase genes under conditions of B defi ciency could directly affect the transmembrane transport and growth by cell elongation. A previous study reported that B defi ciency changed the activity of H + -ATPase but not the abundance of the protein (Ferrol et al, 1993). In contrast, Camacho-Cristóbal and González-Fontes (2007) reported results similar to ours insofar as they also found that B deficiency reduced the level of a plasmalemma H + -ATPase transcript (PMA2) in tobacco roots.…”
Section: Genes Related To Membrane Transportsupporting
confidence: 76%
“…The suppressed expression of the H + -ATPase genes under conditions of B defi ciency could directly affect the transmembrane transport and growth by cell elongation. A previous study reported that B defi ciency changed the activity of H + -ATPase but not the abundance of the protein (Ferrol et al, 1993). In contrast, Camacho-Cristóbal and González-Fontes (2007) reported results similar to ours insofar as they also found that B deficiency reduced the level of a plasmalemma H + -ATPase transcript (PMA2) in tobacco roots.…”
Section: Genes Related To Membrane Transportsupporting
confidence: 76%
“…In the present work we show a rapid decrease of root PMA2 transcript levels under boron deWciency (Fig. 3a), which could imply a drop in the plasmalemma H + -ATPase activity (Schon et al 1990;Ferrol et al 1993) and, as a consequence, a lower nitrate uptake (Fig. 2).…”
Section: Discussionsupporting
confidence: 55%
“…2). In experi- ments with cultures of sunXower cells Ferrol et al (1993) suggested that the regulation of plasmalemma H + -ATPase by boron treatment was due to changes in its activity rather than in the amount of this protein. In addition, in the present work we have observed a strong transcriptional regulation of plasmalemma H + -ATPases by boron deWciency in tobacco roots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The effect on H + pump achievement (ion uptake!) demonstrated in membrane vesicles from B-sufficient and B-deficient sunflower roots may be explained in this way (Ferrol et al 1993). Other functions of B are independent of this, and concern especially the binding of 6-phosphogluconic acid; this leads to a preferred conversion of D-glucose from photosynthesis into cellulose, hemicelluloses, pectins, and lignins.…”
Section: Principles Of Substance Formation and Role Of Nutrient Elementsmentioning
confidence: 96%